Analysis of Operational Performance and Costs of Log Loaders Under Different Conditions - Lima, Cássio Furtado; da Silva, Leonardo França; de Souza, Cristiano Márcio Alves; de Assis Costa Ferreira, Francisco; Minette, Luciano José; Mendieta, Fernando Mateus Paniagua; Lima, Roldão Carlos Andrade; de Freitas, Luís Carlos; Vieira, Jéssica Karina Mesquita; de Oliveira, Victor Crespo [UNESP]; Schettini, Bruno Leão Said; Silva, Arthur Araújo (MDPI, 2025)
The Brazilian forestry sector comprises 9.94 million hectares of plantations, with eucalyptus dominating 75% of this area for pulp production. Technological advances have enhanced machinery performance, with the cut-to-length system being the primary method for pulpwood production. This study aimed to optimize the operational cycle of the log loader by evaluating productivity, operational cycles, and loading costs. Data were collected in Bahia, northeastern Brazil, from a forestry company operating under varying productivity scenarios and forest rotations. Time and motion studies were conducted to assess the log loader’s cycles, while productivity and cost analyses were performed. The results indicated that predictive models effectively explained productivity variations. The log loader’s productivity increased with the average volume per tree (AVT) and decreased with the number of movements, which consumed 68% of the cycle time due to wood adjustment and stack organization. Stages such as personal breaks, truck movements, crane adjustments, and cleaning of fallen material showed no significant statistical differences. Loading costs rose by up to 154% with increased movements and decreased with a higher AVT. Additionally, loading tri-train trucks significantly influenced transportation efficiency, emphasizing the importance of optimizing the log loader’s cycle to balance costs and enhance transportation operations.